Towards Green Markets: Strategies for Enhancing Sustainability in Open-air Popular Markets, Zliten, Libya - Mustafa Ben Hkoma; Hosam Ashokri; Mohamed Fahej; Mohamed Bani; Abdalraoof Alhanbli; Ibtesam Amer; Fatima Maiteeq (AlQalam Journal of Medical and Applied Sciences, 2025)
This study investigates the state of sustainability in open-air popular markets in Zliten city, considering current trends toward establishing green markets that include several environmental aspects. The research originates from a key issue: the limited integration of sustainability standards in organizing these markets, despite their importance in economic and social life. The significance of the study lies in highlighting the vital environmental role of local markets and proposing practical and scientific approaches for their environmental sustainability improvement. The study aimed to assess the current level of sustainability in open-air popular markets, identifying the challenges hindering progress, and suggesting practical strategies for transitioning to green markets, adopting a descriptive-analytical approach. A questionnaire was created, covering three main areas: strategies for enhancing sustainability, the extent to which the green market (sustainability) concept is realized, and the challenges faced in achieving sustainability in open-air popular markets. This tool was distributed to a sample of 100 participants, including vendors, citizens, and regulatory authorities. The statistical analysis results indicated that the state of sustainability remains weak, with the overall average for the sustainability mechanisms dimension at only 2.07 and the average for the realization of the green market concept at 1.91. Administrative and planning challenges, a lack of coordination, and insufficient resources emerged as the main obstacles. The results also confirmed a strong linkage between the availability of environmental infrastructure and the extent of green market realization, compared to the limited influence of awareness programs. The study concluded that adopting integrated strategies to enhance sustainability in open-air popular markets is essential, highlighting the importance of activating coordination and cooperation among stakeholders to ensure a genuine balance between environmental, economic, and social dimensions.